Role of SUMOylation in neurodegenerative diseases - Mandel, Nicolas; Agarwal, Nitin (Cells, 2022)
Neurodegenerative diseases (NDDs) are irreversible, progressive diseases with no effective treatment. The hallmark of NDDs is the aggregation of misfolded, modified proteins, which impair neuronal vulnerability and cause brain damage. The loss of synaptic connection and the progressive loss of neurons result in cognitive defects. Several dysregulated proteins and overlapping molecular mechanisms contribute to the pathophysiology of NDDs. Post-translational modifications (PTMs) are essential regulators of protein function, trafficking, and maintaining neuronal hemostasis. The conjugation of a small ubiquitin-like modifier (SUMO) is a reversible, dynamic PTM required for synaptic and cognitive function. The onset and progression of neurodegenerative diseases are associated with aberrant SUMOylation. In this review, we have summarized the role of SUMOylation in regulating critical proteins involved in the onset and progression of several NDDs.